2010
DOI: 10.1038/hr.2010.232
|View full text |Cite
|
Sign up to set email alerts
|

Pulse wave velocity in primary hyperparathyroidism and effect of surgical therapy

Abstract: The study was aimed at investigating the arterial stiffness assessed by aortic pulse wave velocity (PWV) in the presence of primary hyperparathyroidism (PH), with and without concomitant hypertension. Subsequently, we examined the effect of parathyroidectomy (PTX) on arterial stiffness. A total of 28 patients with PH and concomitant hypertension, and 16 with PH without hypertension were investigated in comparison with 28 essential hypertensive patients and 18 healthy controls, respectively. Patients were match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 26 publications
(40 reference statements)
4
52
0
4
Order By: Relevance
“…It also suggests that PTH could play a role in causing the stiffening of large arteries, as suggested recently. 31 …”
Section: Discussionmentioning
confidence: 99%
“…It also suggests that PTH could play a role in causing the stiffening of large arteries, as suggested recently. 31 …”
Section: Discussionmentioning
confidence: 99%
“…6 Therefore, it has been proposed that increased nitric oxide bioactivity is a compensatory mechanism that counteracts the pressor effects of PTH-induced increases in intracellular calcium. 6 In this issue of the journal, Rosa et al 7 report on their investigation of PPTH patients based on measurements of pulse wave velocity (PWV) before and after surgical treatment of PPTH; PWV is an index of aortic stiffness and hypertension-related target organ damage, which is recommended by the current guidelines of the ESC/ESH as part of the standard evaluation of hypertensive patients because it conveys information that is useful for risk stratification purposes. Interestingly, they found that PWV was higher in PPTH patients than in essential hypertensive patients, which suggests that excess PTH changes the mechanical properties of the arterial walls.…”
Section: P Rimary Hyperparathyroidism (Ppth) Ismentioning
confidence: 99%
“…However, this important finding is not consistent with the results of another recent study from Israel: compared with control subjects who were matched for age, gender and CV risk factors, neither the patients with full-blown (hypercalcemic) PPTH nor those with mild (normocalcemic) PPTH showed increased arterial stiffness, as assessed by several indices, including the PWV. 8 Although these inconsistencies could reflect either a selection bias, involving differences in ethnicity, overall cardiovascular risk profile, stage of PPTH disease in the patients and/or different selection criteria for the controls, it should be emphasized that in the study by Rosa et al, 7 removal of parathyroid adenoma and correction of PPTH were followed by resolution of the increased PWV and a decrease in BP. Therefore, that excess PTH per se has a major detrimental effect on the arterial wall, as shown by increased BP and induced stiffening of the aorta.…”
Section: P Rimary Hyperparathyroidism (Ppth) Ismentioning
confidence: 99%
“…Areal bone mineral density (BMD) (g/cm 2 ; bone mineral content relative to projection area) was measured by DXA (Hologic Discovery W; Hologic Inc., Bedford, MA, USA) at the proximal femur, with a hyperparathyroidism [9][10][11] . Also, Rubin et al 12) found a positive correlation between PTH levels and aortic stiffness in patients with mild primary hyperparathyroidism; however, other studies in patients with primary hyperthyroidism did not confirm the association between PTH levels and aPWV 10,13,14) .…”
Section: Clinical Evaluation and Bone Mineral Densitymentioning
confidence: 99%
“…Exposure to traditional cardiovascular risk factors has been viewed as the key contributor to arterial stiffening 7,8) . Recently, a number of studies have investigated the association between parathyroid hormone (PTH) levels and aortic stiffness in different clinical settings [9][10][11][12][13][14][15][16] . Some studies have found that aPWV is increased in patients with primary…”
Section: Introductionmentioning
confidence: 99%